Effect of medicated mineral mixtures and a pinkeye vaccine on the gain and health of steers grazing native grass pastures - Brazle, F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Feeding supplements containing an antibiotic or ionophore improved stocker gains by .06 to .26 lb per head daily. A combination of Bovatec and Aureomycin in the mineral mixture improved (P<.08) steer gains over feeding Aureomycin alone. Mineral intake was higher than expected for the steers grazing burned, double-stocked) native grass pastures in 1987. Vaccinating steers with Piliguard at turn-out had no effect on pinkeye incidence and reduced stocker gains slightly.
Keywords: Beef; Medicated mineral mixtures; Pinkeye vaccine; Gain; Health